Pelatihan Penulisan Kreatif Sastra Pada Ibu-Ibu Tk Aisyiyah - Firdaus, Asep; Setiadi, David; Humaira, Hera Wahdah (PT. Alahyan Publisher Sukabumi, 2024)
Creative Writing Mentoring through the Zoom Meeting platform on February 24, 2024, is a valuable initiative aimed at developing literary creativity among the kindergarten teachers of Aisyiyah in Sukabumi Regency. The activity was opened by the Chairperson of the Education Council of the Aisyiyah Women's Association (PDA) of Sukabumi Regency, Mrs. Sistiana Windyariani, M.Pd., and attended by 7 participants consisting of Aisyiyah kindergarten teachers. During the seminar and training session, Den Aslam introduced the basic concepts of creative writing and techniques to enhance creativity. Discussions were also held on writing techniques, including character development, plot, and effective language usage, accompanied by examples of prophetic-themed poetry. Participants were allowed to practice writing using these techniques for approximately 2 weeks. The low level of participant engagement in asking questions and the limited number of participants served as feedback for bettering future engagement activities. This activity is expected to significantly benefit participants in developing their creative writing skills and enhancing their appreciation for literature.